1986
DOI: 10.1135/cccc19861609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the rate of stirring on crystal size in precipitating or salting-out systems

Abstract: A simple model is proposed to express the dependence of the mean crystal size on the rate of stirring in precipitating or salting-out systems. The nucleation rate is taken to be proportional to the interfacial area of segregated regions. This area is a function of the dissipated energy. The derived relations are applied to results of a series of experiments in which aluminium-potassium sulphate was salted out by the addition of aqueous solutions of methyl alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We return to this point at the end of the paper. A few studies of mixing effects in semibatch crystallizers have also been reported (Nyvlt and Zacek, 1986;Pohorecki and Baldyga, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…We return to this point at the end of the paper. A few studies of mixing effects in semibatch crystallizers have also been reported (Nyvlt and Zacek, 1986;Pohorecki and Baldyga, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…However, no influence of stirring speed on the mean size of nanoparticles formed was observed in the experimental study of drowning out of ethylcellulose . For the crystallization of griseofulvin by compressed carbon dioxide as an antisolvent, and the salting out of KAl(SO 4 ) 2 , it was experimentally observed that the mean crystal size decreased with increasing stirring rate. Such opposing observations can be attributed to the different kinetics of each individual system.…”
Section: Resultsmentioning
confidence: 95%
“…6,7 Various experimental studies of antisolvent crystallization in an agitated semibatch vessel indicate that the crystal size distribution (CSD) depends strongly on the operating conditions, such as agitation rate, mode of addition (direct or reverse), addition rate, solvent composition, and size of the crystallizer. 5,[8][9][10][11][12][13][14][15][16][17][18][19][20] The polymorphic or pseudopolymorphic form can also depend on the operating conditions. [21][22][23][24][25][26] Most variations in the operating conditions have a direct influence on the mixing of the antisolvent and the solution, which affects the localized supersaturation and, thus, the crystal product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experimental studies of antisolvent crystallization in an agitated semibatch vessel indicate that the crystal size distribution (CSD) depends strongly on operating conditions such as agitation rate, mode of addition (direct or reverse), addition rate, solvent composition, and size of the crystallizer [3,[19][20][21][22][23][24][25][26][27][28][29][30][31]. The polymorphic or pseudopolymorphic form can also depend on the operating conditions [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%